LETTER PUPPET GAME AS A MEDIA FOR EARLY CHILDHOOD LITERACY STIMULATION - Erna Budiarti; Nanik Rahayu; Usup Usup; Mia Sumiani Madi; Sitti Zaifan; Andi Ernawati (Sean Institute, 2022)
The Wayang Letter game is an interesting learning medium for children, especially in early childhood. In the Wayang Letter game, children are given direct experience because they are actively involved in playing according to the creativity of each child. Children who are known by various early literacy letters as the basic steps of children's reading literacy. The characters in the wayang letters can be packaged into children's favorite characters and can be played with a variety of storylines. In addition to interesting games, the Wayang Letter game developed at TK Widya Kusuma Sari Denpasar comes from materials that are easily available and also easy to make. The Wayang Letter game can be used as a parenting activity because it is easy to apply or play at each child's home together with their parents. This article aims to describe how the Wayang Letter game can provide benefits for the introduction of literacy as a step in developing children's reading literacy. The method used to analyze the data is qualitative analysis techniques, namely by collecting information and observing through observation and also in-depth analysis with various related sources.